2017
DOI: 10.1111/ajt.13966
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Kidneys From Donors With Acute Kidney Injury: Friend or Foe?

Abstract: The gap between supply and demand in kidney transplantation has led to increased use of marginal kidneys; however, kidneys with acute kidney injury are often declined/discarded. To determine whether this policy is justified, we analyzed outcomes of donor kidneys with acute kidney injury (AKI) in a large UK cohort. A retrospective analysis of the UK Transplant Registry evaluated deceased donors between 2003 and 2013. Donors were classified as no AKI, or AKI stage 1-3 according to Acute Kidney Injury Network (AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(168 citation statements)
references
References 27 publications
9
153
4
2
Order By: Relevance
“…Similar to other studies that have reported on transplanting kidneys from donors with AKI, our study found a high rate of delayed graft function with satisfactory long‐term graft function …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies that have reported on transplanting kidneys from donors with AKI, our study found a high rate of delayed graft function with satisfactory long‐term graft function …”
Section: Discussionsupporting
confidence: 91%
“…However, a US Scientific Registry of Transplant Recipients Report found an association with higher graft loss in expanded criteria donor kidneys but not standard donor criteria kidneys when there was more severe AKI as evidenced by higher donor serum creatinine levels . A further large registry study from the UK found that AKI was associated with delayed graft function but also inferior graft function and a small reduction in graft survival at 1 year; more severe grades of AKI were associated with primary non‐function …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported similar results; Hall et al reported that the incidence of DGF increased with the AKI stage (34%, 52%, and 57% in the Risk, Injury, and Failure stages, respectively, P < 0.001) . In a retrospective analysis of the UK Transplant Registry comprising 11 649 donors with 10 years of follow‐up, the incidence of DGF increased with the AKI stage (OR: 1.33, 95% CI: 1.15‐1.54 for stage 1; OR: 1.67, 95% CI: 1.37‐2.03 for stage 2; OR: 2.98, 95% CI: 2.25‐3.96 for stage 3) . The author also reported statistically significant differences in 1‐, 3‐, and 5‐year graft survival between recipients who received kidneys from donors with and without AKI; however, the survival rate was only 2% lower and the absolute reduction in eGFR was only 1.6 mL/min/1.73 m 2 with AKI, which was uncertain to have clinical significance.…”
Section: Discussionmentioning
confidence: 52%
“…Multiple single‐center studies have demonstrated that kidneys transplanted from donors with AKI, typically defined as a terminal creatinine ≥2.0 mg/dl, have an increased risk of delayed graft function (DGF), with greater risk of DGF seen with more severe AKI . Despite the increased risk of early complications, these kidneys are associated with excellent allograft survival and allograft function in the short term, even with increasing severity of AKI in the donor [.] However, the majority of kidney transplants included in these studies had cold ischemia time (CIT) <24 h.…”
Section: Introductionmentioning
confidence: 99%